Influência do pH e da temperatura sobre os efeitos do cobre no sangue e fígado de curimbatá, Prochilodus scrofa, (STEINDACHNER, 1881) - Carvalho, Cleoni dos Santos (Universidade Federal de São Carlos, 2003)
Considering that the pollutants in fish and other animals begin at enzymatic levels, and may alter the cell function and structure, the main goal of the present study was to analyze the influence of the water pH and temperature on the copper effects in liver and blood of the freshwater fish, Prochilodus scrofa via hematological, morphological and enzymatic analysis. Juveniles specimens of P. scrofa acclimated to 20 and 30ºC were exposed to copper (acute exposure) in static systems at water pH 4.5 and 8.0 to determine the 96h-LC50. Them groups of fish were exposed to 96h-LC50 in the same water conditions for hematological analysis, determination of activity of regulatory and associated glycolitic enzymes from liver and blood in vivo and in vitro and liver morphological analysis. Groups of fish acclimated at 20 and 30ºC were kept a water pH 7.0 and serve as control for the controls groups pH 4.5 and 8.0. The 96h-LC50 were calculated as 98 ± 0.9 and 16 ± 0.2 µgCu.L-1 respectively at pH 4.5 e 8.0 a 20ºC and 88 ± 0.8 e 14 ± 0.5 µgCu.L-1 em pH 4.5 e 8.0 a 30ºC. The change in water pH caused na increase in the hematocrit (Hct) in both water pH and temperatures, reduction of hemoglobin concentration ([Hb]) at water pH 4.5 at 20 and 30ºc and an increase in the number of erythrocytes (RBC) at pH 4.5 at 30ºC (p<0.05). Copper exposure caused an increase in [Hb] and RBC at 20ºC in both pHs and a reduction in the [Hb] at pH 4.5 and RBC at pH 8.0 a 30ºC. In vivo studies showed an increase in the plasma glucose concentration of the control group pH 4.5 and in fish exposed to copper in pH 4.5 at 30ºC (p<0.05). Hepatic glycogen concentration was higher at 20ºC (p<0.05). The activity of PFK enzyme in liver was reduced in the control group pH4.5 at 20ºC and increased after copper exposure. In vitro studies showed high influence of temperature on the regulatory enzymes. The activity of HK, PFK, PK, LDH and G6PHD was reduced in the control groups at 30ºC. After copper exposure the activity of these enzymes increased reaching values similar of the controls pH 7.0. In the erythrocit the increase of enzyme activity after copper exposure was more evident in the HK and PFK enzymes. Copper accumulation in liver was higher at 20ºC however, the metallothionein induction that was isolated using DEAE-Sepharoese and identified by SDS-PAGE, was more evident in fish exposed to low copper concentration in water but pH 8.0 (LC50-96h at water pH8.0). Liver histopathologies (hyperemia, cytoplasmic vacuolization, cellular and nuclear degeneration, focal necrosis and melanomacrophages) in P. scrofa was more related to the changes in water pH than copper exposure. These results evidenced that the changes in hematology and in the enzyme activities in response to pH and copper in the environment are complex. However, it is possible to conclude that: 1) the anaerobic metabolism prevailed in liver in fish acclimated to 20ºC, in vivo, while, in vitro, the enzyme activity was kept without change, except for HK and PK that increased their activity. The activity decrease of the regulatory and associated enzymes suggest the use of glycolitic via for energy at 30ºC; 2) copper decrease the activity of these enzymes in both temperatures; 3) the activities of regulatory enzymes at 20ºC, in the erythrocit from control groups, in vivo, suggest the mobilization of glucose. Copper addition in it showed activity stimulation in low pH (PFK) and inhibition in high pH (PFK) suggesting that in this pH the energy probably come from lactate produced by the LDH; 4) in the erythrocit, at 20ºC, the pH and copper effect suggest that the aerobic metabolism was stimulated at low pH and that the anaerobic metabolism was stimulated at high pH; it was evidenced by the increase of PFK and LDH activities, respectively; 5) the energetic demand at high temperature was maintained by the activity of PFK and LDH in the control groups and in the presence of copper prevailed the anaerobe at low pH and the aerobe at high pH; 6) the increase of metallothionein concentration suggests an increase of metabolism with the increase of temperature that increased the synthesis of this protein and the higher accumulation of copper at 20ºC may evidence higher copper excretion in fish acclimated to 30ºC; 7) the more frequent changes in the hepatic tissue found in all experiments showed low specificity of lesions as most of them occurred in response to change in water pH.
Keywords: Bioquímica; Enzimas glicolíticas; Metalolionina; Hematologia; Histologia (tecido); Prochilodus scrofa; CIENCIAS BIOLOGICAS